Answer:
11 - 3x = 75 - -1x
X = -16
Hope this helps
:0 can I have brainliest
Step-by-step explanation:
Answer:
see explanation
Step-by-step explanation:
The sum of the 3 angles in a triangle = 180°, thus
∠1 = 180° - (72 + 57)° = 180° - 129° = 51°
The right angle at the left vertex is composed of 72° and ∠2, thus
∠2 = 90° - 72° = 18°
57° and ∠3 form a straight angle and are supplementary, thus
∠3 = 180° - 57° = 123°
∠4 = 180° - (∠2 + ∠3 ) ← sum of angles in a triangle
∠4 = 180° - (18 + 123)° = 180° - 141° = 39°
Answer:
57 + x³
Step-by-step explanation:
5u - (-20u) - u - 18u + (-11u) = 10
5u + 20u - u - 18u - 11u = 10
-5u = 10
-5(-2) = 10
So, in conclusion, X, is equal to -2.
F(x) = x^5 - 1; g(x) = 5x^2; h(x) = 2x
Answer: